(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This article discusses some theoretical aspects of the formation of cognitive competence of future teachers of initial pre-conscription training in the conditions of problem-based learning. The main provisions in military professional training are determined, the areas of implementation of the cognitive competence of future teachers of initial pre-conscription training are presented.